New urban spaces urban theory and the scale question - Brenner, Neil (Oxford University Press, 2019)
In New Urban Spaces, Neil Brenner proposes a radical reconceptualization of inherited approaches to urbanization. Rather than focusing on cities as bounded units, urbanization is conceived here as multiscalar. Drawing on the methods of critical geopolitical economy, especially the writings of Henri Lefebvre, Brenner systematically elaborates this multiscalar conceptualization of the capitalist urban fabric in order to investigate emergent patterns and pathways of urban restructuring.